Alpha-Synuclein: From Early Synaptic Dysfunction to Neurodegeneration - Ghiglieri, Veronica; Calabrese, Valeria; Calabresi, Paolo (Frontiers in Neurology, 2018)
Over the last two decades, many experimental and clinical studies have provided solid evidence that alpha-synuclein (α-syn), a small, natively unfolded protein, is closely related to Parkinson’s disease (PD) pathology. In order to provide an overview on the different roles of this protein, here we propose a synopsis of seminal and recent studies that explored the many aspects of α-syn. Ranging from the physiological functions to its neurodegenerative potential, the relationship with the possible pathogenesis of PD will be discussed. Close attention will be paid on early cellular and molecular alterations associated to the presence of α-syn aggregates.